Violência escolar na perspectiva dos professores participantes dos círculos de construção de paz - Passeri, Helen Jane (2021)
Violence has always accompanied the historical and evolutionary process of the human being, becoming over the centuries an object of study in the humanities and health sciences. One of the scenarios of violence refers to the school environment and the efforts made in its understanding, complexity and entanglements. Nowadays it is still a great challenge not only for Brazil, but for the world, to prevent violence, given the countless cases of violence among the school community and even the massacres reported by the media. Thus, this research aimed to identify the impact of school violence on teaching from the perspective of teachers participating in the Peacemaking Circle. This is research with a qualitative approach carried out with seven teachers from four State Public Schools in Foz do Iguaçu, Paraná, working in the final years of elementary school and high school. The research information was collected through direct observation and application of the Peacemaking Circle technique, derived from Restorative Justice. The invitation to the teachers was made through educators from state schools in the municipality and through the participation of the researcher in a teachers' meeting promoted by the Paraná Public Education Workers Union - APP / FOZ. The selection of participants occurred based on the availability of time for teachers who volunteered. Peacemaking Circles took place according to the methodology proposed by Kay Pranis (2010), adapted to the online format due to the need for social distancing due to the Covid-19 pandemic. There were five meetings, one of which was an initial interview, three collective meetings of Peacemaking Circles which were videotaped and a final individual meeting for feedback on the activity. Data analysis took place through a qualitative and phenomenological epistemology, using the participants' narratives as analysis material. The results showed that the various forms of school violence have a negative impact on teaching, contributing to the removal of the function of teachers, causing suffering and lack of interest in the profession. As for the technique of Peacemaking Circles used for data collection, it was very well accepted by teachers with the possibility of being used in the classroom as an action to prevent violence.